2019
DOI: 10.1021/acsanm.9b01590
|View full text |Cite
|
Sign up to set email alerts
|

SiC Nanowire Sponges as Electropressure Sensors

Abstract: Light-weight, flexible and highly porous ceramic are very attractive to engineering applications due to their good inertness, stable and excellent mechanical properties. We here report such SiC nanowire (SiCNW) sponges and demonstrate their multi-functionalities. They were simply generated by reacting SiO2 with the sustainable kitchen sugar, using NH4Cl as a blowing agent. The as-grown highly porous SiCNW sponges exhibit a core-shell structure, with an extremely low density in the range of 115-125 mg/cm 3 (aga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 39 publications
(57 reference statements)
0
13
0
Order By: Relevance
“…In fact, conventional manufacturing of flexible functional materials, including iontronic materials, liquid metals, and conductive polymers doped with micro-/nanoparticles, inevitably results in fluctuations in their conductivity because of strain. 79–86 Hence, a thorough examination of strategies for stretch insensitivity is needed to better understand the aspects related to strain.…”
Section: Emerging Concepts For Mechanical and Electrical Designs Of U...mentioning
confidence: 99%
“…In fact, conventional manufacturing of flexible functional materials, including iontronic materials, liquid metals, and conductive polymers doped with micro-/nanoparticles, inevitably results in fluctuations in their conductivity because of strain. 79–86 Hence, a thorough examination of strategies for stretch insensitivity is needed to better understand the aspects related to strain.…”
Section: Emerging Concepts For Mechanical and Electrical Designs Of U...mentioning
confidence: 99%
“…Thus, the method is relative simple, efficient, energy and material economic, and versatile. Zhu et al [156] used in-situ template and NH 4 Cl foaming method to prepare SiC foam (Fig. 7f), which was successfully used in the field of pressure sensors by virtue of its high elastic conductivity.…”
Section: Carbide Aerogelsmentioning
confidence: 99%
“…[194] Xia et al reported a SiC nanowire (SiCNW) sponge with low density (115 -125 mg/cm 3 ), good mechanical properties (compressive modulus of about 1.35 MPa) and electromechanical induction (gauge factor up to 87). [156] In addition, the thermal conductivity of SiCNW sponge at room temperature is low, about 1.01 W/mK, indicating that it has a certain potential to monitor structural damage or capture impact in high-temperature environments.…”
Section: Applications Of Htrasmentioning
confidence: 99%
“…[256][257][258][259][260] However, the fabrication of high-performance pressure sensors based on WBG semiconductor nanowires, especially for SiC, group III-nitrides, and diamond, are very rare. [261][262][263] For instance, Phan et al reported an effective approach to develop highly sensitive pressure sensors employing 3C-SiC nanowires fabricated at the center of a dogbone-like structure. [261] Figure 12a shows a photograph of SiC nanowire-based pressure sensors mounted on an acrylic holder.…”
Section: Pressure Sensorsmentioning
confidence: 99%
“…Very recently, Chen et al., developed lightweight SiC nanowire sponges via the simple sugar‐blowing‐assisted carbothermal reduction. [ 262 ] Their experimental results showed an excellent pressure‐dependent electrical response. The electrical resistance decreased with the rise of the applied load but completely recovered upon unloading (Figure 12e).…”
Section: Applications For Environmental Monitoringmentioning
confidence: 99%